Requirement for CD40-CD40 Ligand Interaction for Elimination of Cryptosporidium parvum from Mice - Cosyns, Mary (American Society for Microbiology, 1998)
Mice with disrupted genes for CD40 and CD40 ligand (CD40L) are unable to clear infection with Cryptosporidium parvum and develop cholangitis. Parasites are present in the gut, gall bladder, and biliary tree, and biliary epithelial cells express CD40 on the cell surface. SCID mice infected with C. parvum for >1 month can clear the infection after reconstitution with spleen cells from CD40, but not CD40L, knockout mice. In an in vitro model, C. parvum-infected HepG2 cells were triggered to apoptosis when incubated with a CD40L-CD8 fusion protein. The requirement for CD40-CD40L interactions for immunity to C. parvum indicated by our results may entail the triggering of apoptosis in infected cells, in addition to the known role of CD40L-CD40 interactions in stimulating cytokine production and promoting T-cell responses.